The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the Proceedings of 1st Workshop on Environmental Science, Society, and Technology, WESTECH 2018, December 8th, 2 2019
DOI: 10.4108/eai.8-12-2018.2283941
|View full text |Cite
|
Sign up to set email alerts
|

Higher Order Thinking Skills (HOTS) in GUSJIGANG Culture and Character of Kudus People

Abstract: This article aims to explore the correlation or association of"gusjigang" culture with high-level thinking skills. This research was conducted by employing a phenomenological method the main observation subject of which was the activities of Kudus Kulon residents as the epicenter of the development of the gusjigang culture and the development of Islamic civilization led by Sunan Kudus. The advantage of this research is the acquisition of information about the relationship between higher order thinking skills a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
0
0
2
Order By: Relevance
“…Guru juga dapat mengangkat potensi local di daerahnya. Penelitian yang dilakukan oleh (Utaminingsih & Murtono, 2019) menemukan bahwa integrasi muatan local efektif meningkatkan kemampuan berfikir kritis siswa. Adapun hasil penelitian tersebut mengatakan, "Based on the results of the study, it can be concluded that the character of"gusjigang" contains important components of high-level thinking skills.…”
Section: Pembahasanunclassified
“…Guru juga dapat mengangkat potensi local di daerahnya. Penelitian yang dilakukan oleh (Utaminingsih & Murtono, 2019) menemukan bahwa integrasi muatan local efektif meningkatkan kemampuan berfikir kritis siswa. Adapun hasil penelitian tersebut mengatakan, "Based on the results of the study, it can be concluded that the character of"gusjigang" contains important components of high-level thinking skills.…”
Section: Pembahasanunclassified
“…Berdasarkan uraian permasalahan dan fakta-fakta tersebut perlu ada upaya dan kreatifitas, khususnya pengelolaan pembelajaran diantaranya yaitu menggunakan model pembelajaran yang menekankan kemampuan berpikir kritis, pemecahan masalah, kreatifitas siswa dan menyenangkan. Students need learning development, one of the possible developments is to develop teaching models that match characteristics to make learning more interesting and enjoyable (Wibowo et al, 2019).…”
Section: Pendahuluanunclassified